2023
DOI: 10.3389/fnins.2023.1064890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of closing material on hearing rehabilitation in stapedectomy and stapedotomy: A finite element analysis

Abstract: Stapedotomy or stapedectomy operations are often performed to treat otosclerosis. During the operation, the space created by bone removal is usually filled with a closing material such as fat or fascia. In this study, the effect of the Young’s modulus of the closing material on the hearing level was investigated through the 3D finite element model of a human head including auditory periphery. The Young’s moduli of the closing material used to implement stapedotomy and stapedectomy conditions in the model were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…An older study comparing gelfoam, fat tissue, and fascia showed an incidence of perilymphatic fistula of 3.5% in case of gelfoam, 1.9% in case of fat tissue, and 0.6% in the case of fascia [ 74 ]. According to Lim et al [ 75 ], from an auditory point of view fatty tissue is to be preferred in stapedotomy and fascia in stapedectomies.…”
Section: Late Postoperative Vertigomentioning
confidence: 99%
“…An older study comparing gelfoam, fat tissue, and fascia showed an incidence of perilymphatic fistula of 3.5% in case of gelfoam, 1.9% in case of fat tissue, and 0.6% in the case of fascia [ 74 ]. According to Lim et al [ 75 ], from an auditory point of view fatty tissue is to be preferred in stapedotomy and fascia in stapedectomies.…”
Section: Late Postoperative Vertigomentioning
confidence: 99%